2019
DOI: 10.1021/acs.est.9b06119
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Maternal Transfer of Mercury in Birds: Implications for Altered Toxicity Risk

Abstract: Maternal transfer is a predominant route of methylmercury (MeHg) exposure to offspring. We reviewed and synthesized published and unpublished data on maternal transfer of MeHg in birds. Using paired samples of females’ blood (n = 564) and their eggs (n = 1814) from 26 bird species in 6 taxonomic orders, we conducted a meta-analysis to evaluate whether maternal transfer of MeHg to eggs differed among species and caused differential toxicity risk to embryos. Total mercury (THg) concentrations in eggs increased w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 63 publications
(114 reference statements)
1
15
0
Order By: Relevance
“…2−4 The toxicological risks of MeHg to aquatic and terrestrial organisms are governed by in vivo transformations, intertissular exchanges, and depuration rates and pathways of MeHg and other biologically relevant forms of mercury. 1 In birds, MeHg can be demethylated in the liver, 5,6 depurated into feathers during molt or to offspring by maternal transfer, 7 and excreted. 1 Stable isotope ratios of mercury are a central tool for ecologic risk assessment and mercury source apportionment to organisms, 8−14 yet critical questions remain on the isotopic fractionation of mercury by in vivo transformations.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2−4 The toxicological risks of MeHg to aquatic and terrestrial organisms are governed by in vivo transformations, intertissular exchanges, and depuration rates and pathways of MeHg and other biologically relevant forms of mercury. 1 In birds, MeHg can be demethylated in the liver, 5,6 depurated into feathers during molt or to offspring by maternal transfer, 7 and excreted. 1 Stable isotope ratios of mercury are a central tool for ecologic risk assessment and mercury source apportionment to organisms, 8−14 yet critical questions remain on the isotopic fractionation of mercury by in vivo transformations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Higher trophic level organisms (e.g., birds, fish, and mammals) are exposed to methylmercury (MeHg) through dietary sources, which is assimilated in the digestive tract, circulated in the bloodstream, and retained in the protein of tissues as a MeHg–cysteine complex (MeHg–Cys). The toxicological risks of MeHg to aquatic and terrestrial organisms are governed by in vivo transformations, intertissular exchanges, and depuration rates and pathways of MeHg and other biologically relevant forms of mercury . In birds, MeHg can be demethylated in the liver, , depurated into feathers during molt or to offspring by maternal transfer, and excreted . Stable isotope ratios of mercury are a central tool for ecologic risk assessment and mercury source apportionment to organisms, yet critical questions remain on the isotopic fractionation of mercury by in vivo transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Organochlorine compounds, such as DDT (dichlorodiphenyltrichloroethane), were widely used beginning in the 1940s and were found to decrease eggshell thickness and affect egg survival (Cooke, 1973; Hickey & Anderson, 1968). It is possible that Hg within the egg itself, which also indicates Hg within the female developing the egg (Ackerman et al., 2020), may also influence eggshell thickness, but studies are less conclusive for this contaminant. We found that eggshell thickness, measured either at the equator or the sharp pole, was not correlated with egg content THg concentrations.…”
Section: Discussionmentioning
confidence: 99%
“… 58 61 The toxicological risk of MeHg to birds is ultimately governed by the intake of dietary MeHg relative to internal demethylation of MeHg and depuration of solely MeHg into feathers during molt 62 or to offspring by maternal transfer. 63 Environmental studies of birds using stable Hg isotopes provide critical toxicological information on the above-mentioned processes and highlight the need to consider internal transformations of Hg when Hg stable isotopes are used to source- or process-track Hg in the environment. As such, birds have been proposed to behave as open isotope systems with continuous inputs of MeHg (the “reactant”), several internal transformations that induce isotopic fractionation in products, and selective depuration of primarily MeHg.…”
Section: Mercury Isotope Dynamics In Biotamentioning
confidence: 99%